Association analysis of MALAT1 polymorphisms and risk of psoriasis among Iranian patients. (30th November 2021) - Ghafouri‐Fard, Soudeh; Gholipour, Mahdi; Abak, Atefe; Hussen, Bashdar Mahmud; Kholghi Oskooei, Vahid; Taheri, Mohammad; Rakhshan, Azadeh
Abstract: MALAT1 is a long non‐coding transcript that affects immune reactions, thus being involved in the pathoaetiology of immune‐related conditions. We investigated the associations between two genetic variants in MALAT1 and susceptibility to psoriasis in the Iranian population. The G allele of rs619586 has been shown to be less common among cases versus controls (odds ratios (OR; 95% confidence intervals (CI)) = 0.57 (0.36–0.9)), adjusted p = .02). This single nucleotide polymorphism has been associated with the risk of psoriasis in a dominant model (AG + GG vs. AA: OR (95% CI) = 0.56 (0.35–0.92), adjusted p = .04) as well as log‐additive model (OR (95% CI) = 0.59 (0.38–0.92), adjusted p = .04). The rs3200401 was not associated with psoriasis in any of the supposed inheritance models. This study potentiates rs619586 as a risk locus for psoriasis in the Iranian population.